Purpose, Values and Governance in Big Tech Companies - Blanaid Clarke (Bond Law Review, 2022)
The private decisions of the five “Big Tech” (“BT”) companies (Facebook, Apple, Alphabet Inc, Amazon and Microsoft) have very public results as they play a significant role in social, economic and political life. This article explores the purpose of these companies in the context of the current debate about corporate purpose in order to understand their role in society and to explore how they should be governed. The concept of “purpose” has a number of meanings depending on the different contexts and the different disciplines involved in the study. Part II of the article examines the notion of corporate purpose which forms part of a wide-ranging and topical debate as to the interests which should be taken into account by boards in making operational decisions. Often the choice in managing or overseeing the management of the company is framed as a binary choice between acting in the interests of shareholders or acting in the interests of broader stakeholder constituents. In reality, the issue is more nuanced and complex and the quest for an answer extends into a discussion of company law obligations and directors’ duties. The positioning of BT companies in relation to this understanding of purpose is then reviewed. Part III of the article examines what may be viewed as a managerial corporate purpose concept. This constitutes a tool to guide management and to signal “the direction and the reason for the company's existence”. The use by BT companies of this tool is explored and its usefulness evaluated. Finally, Part IV of the article considers three policy proposals which might be considered in the area of corporate governance: the application of board suitability requirements; the introduction of a public benefit purpose and the use of public interest directors.